Jorge baron's show as paradigm of cultural neo-populism in the colombian television (2010)
This article comes from the investigation field of the Stars Show (El Show de las Estrellas), the oldest and most popular musical TV show in Colombian television. The case analysis is an excuse to reframe the discussion on cultural policies in the context, apparently paradoxical, of structural violence, privatization and peak of the right populism that characterizes the Colombian politics in the last years.